Uso de la red social facebook como estrategia de aprendizaje en los estudiantes del 3er año de bachillerato del Instituto Tecnológico Vicente León - Osorio Martínez, Jessica Clarivel (2015)
The present research work focuses on the use of the social network site Facebook as a learning strategy in the students in the 3rd year of secundary education of Vicente Leon Technological Institute. This thesis is developed through the review, analysis and reflection of the various theories, following the history of social network, Facebook, new learning tool etc. The TIC are part of the society, since it has become a tool that permit the collaborative learning that involves spaces of interaction and, at the same time, encourages self-learning between students and teachers inside and outside the classroom. For this reason, it is necessary to consider that the social network site Facebook is a platform suitable that can be to in benefit of education, through this research is was irasubmiting various aspects that are analyzed through of this thesis….